2020
DOI: 10.21203/rs.2.17787/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Baseline Low ALT Activity, a Marker of Sarcopenia and Frailty, is Associated with Increased Long-Term Mortality after COPD Exacerbations. Historic Prospective Cohort Study.

Abstract: Background. COPD exacerbations have negative impact on patients' survival. Several risk factors for grave outcomes of such exacerbations have been descried. Muscle dysfunction and mass loss were shown to impact negatively on prognosis and survival. Low activity of the enzyme ALT (Alanine amino-transferase) in the blood is a known indicator for sarcopenia and frailty, however, no previous studies addressed the association of low ALT amongst patients hospitalized due to COPD exacerbation and long-term survival. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Our analysis suggested that the levels of ALT were inversely associated with COPD risk. Previous studies also reported that low ALT levels play an important role in COPD development and exacerbations (9,17). In clinical practice, circulating ALT levels commonly represent a specific liver dysfunction and injury marker.…”
Section: Discussionmentioning
confidence: 94%
“…Our analysis suggested that the levels of ALT were inversely associated with COPD risk. Previous studies also reported that low ALT levels play an important role in COPD development and exacerbations (9,17). In clinical practice, circulating ALT levels commonly represent a specific liver dysfunction and injury marker.…”
Section: Discussionmentioning
confidence: 94%